(untitled) (Research, Society and Development, 2022)
Objective: COVID-19 is a respiratory infection that demands long-term use of invasive mechanical ventilation, resulting in a reduced capacity of the respiratory muscles. Studies have shown that telerehabilitation brings similar results to traditional pulmonary rehabilitation. Methodology: The aim of the study was to verify the satisfaction and compliance of Post-COVID-19 patients with telerehabilitation and to analyze whether telerehabilitation is effective in reducing dyspnea and improving quality of life. This is a prospective clinical trial study composed of 36 participants with respiratory infection confirmed by COVID-19 by PCR. Results: The protocols of maximum sustained inspiratory pressure assessment, strength index assessment, inspiratory muscle endurance capacity assessment, Likert Scale and telerehabilitation protocol were applied. Conclusion: It was found that at the beginning the participants did not believe that the treatment would work, bring results, improve fatigue symptoms, or help them perform the activities of basic living. After 30 days of treatment, the average satisfaction was 93.1% compared to 65.6% initially. It was possible to conclude that there was a significant increase in satisfaction, adherence, improvement in functional capacity, and reduction in dyspnea through telerehabilitation.